2014
DOI: 10.1111/1759-5436.12097
|View full text |Cite
|
Sign up to set email alerts
|

Business Borderlands: China's Overseas State Agribusiness

Abstract: In the context of widespread interests in China's agro-state-owned enterprises (SOEs), this article starts demystifying four narratives prevailing internationally. In this intellectual landscape, the article coins an innovative approach, 'farm as business borderland' to investigate an agro-SOE in Tanzania. Based on the ethnographic case study, the article presents the tensions arising between the case farm and its Beijing headquarters on the one hand, and between Chinese managers and local stakeholders on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, it faces problems such as shortage of financial strength and poor ability to resist risks. It is undeniable that state-owned enterprises occupy an important position in China's agricultural FDI [47]. Although the number of state-owned enterprises is small, investment flow accounts for nearly 50% of the total, the state-owned enterprises are heavily involved in overseas investment [42].…”
Section: Characteristics Of China's Agricultural Fdimentioning
confidence: 99%
See 1 more Smart Citation
“…However, it faces problems such as shortage of financial strength and poor ability to resist risks. It is undeniable that state-owned enterprises occupy an important position in China's agricultural FDI [47]. Although the number of state-owned enterprises is small, investment flow accounts for nearly 50% of the total, the state-owned enterprises are heavily involved in overseas investment [42].…”
Section: Characteristics Of China's Agricultural Fdimentioning
confidence: 99%
“…Although the number of state-owned enterprises is small, investment flow accounts for nearly 50% of the total, the state-owned enterprises are heavily involved in overseas investment [42]. The advantage of state-owned enterprises lies in rich experience and strong ability to integrate resources in overseas investment [47]. But they are subject to more government supervision, inflexible management systems, and less investment awareness.…”
Section: Characteristics Of China's Agricultural Fdimentioning
confidence: 99%
“…With no direct affiliation, the Department could only exercise control over this overseas business through Lv Qingwen. Accounting for this lack of formal economic control, their over-reliance on a few managers and the false assumption that an SOE headquarters can closely monitor economic activities and day-to-day operations of its overseas subsidiaries (Xu et al 2014), the leaders of the Department might have had only a vague idea of how 'their' Russian companies were operating. For example, the director deliberately prevented a meeting between Du Wenjuan and the Department's head, thereby preventing his superiors from learning about Zhu Fengwang's death.…”
Section: Case 1: a State-owned Farm And A Commercial Farmermentioning
confidence: 99%
“…A great number of them are reported to go bankrupt despite substantial government subsidies (He 2014). Meanwhile, it is reported that until 2014, more than 1.4 million rural cooperatives have been built and that the involved rural households are amounting to100 million (Li 2014). However, 80-95 percent of them are considered as 'fake cooperatives' (Liu 2010).…”
Section: Figure 1 Schema Of Current Agricultural Production Modalitimentioning
confidence: 99%
“…China's state-owned enterprises (SOE) had turned into independent market players since the 1990s when the market-oriented reform started (Xu et al 2014). Since the ABCD food companies 23 control about percent of the grain trade in the world, and also have great power in the global sugar and oil market (Murphy and Clapp 2012).…”
Section: Changes In Agricultural Production Factors and China's Role mentioning
confidence: 99%